2015
DOI: 10.1016/j.jpowsour.2014.12.093
|View full text |Cite
|
Sign up to set email alerts
|

In-situ diagnostic tools for hydrogen transfer leak characterization in PEM fuel cell stacks part I: R&D applications

Abstract: h i g h l i g h t sIn-situ diagnostic tool to quantify hydrogen transfer leaks in PEM fuel cell stacks. Closed form relationship for the rate of hydrogen transfer leak. Requires hydrogen/nitrogen supply to anode/cathode with anode overpressure. Requires pressure, flow, temperature, humidity, and OCV measurements. Accurately estimates leak in each cell of a stack, suitable for R&D applications. a b s t r a c tThis paper describes a diagnostic tool for in-situ characterization of hydrogen transfer leak in indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…In this manner, all the hydrogen permeating through PEM is converted into a limiting hydrogen oxidation current (i.e., hydrogen crossover current), which is equivalent to the hydrogen crossover rate, and the key to the measurement is to isolate this component from the total current. Linear sweep voltammetry (LSV) is the most commonly used potential sweep technique in measuring hydrogen crossover (Brooker et al, 2012;Giner-Sanz et al, 2014;Huang et al, 2013;Hwang et al, 2018;Kocha et al, 2006;Niroumand et al, 2015;Wasterlain et al, 2011), but different scan rates always give rise to inconsistent results. Another electroanalytical method as a derivative of LSV is staircase voltammetry (also called as potential step method [PSM]), in which the potential sweep is a series of stair steps, and it has been employed in electrochemical measurements of hydrogen crossover (Schoemaker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, all the hydrogen permeating through PEM is converted into a limiting hydrogen oxidation current (i.e., hydrogen crossover current), which is equivalent to the hydrogen crossover rate, and the key to the measurement is to isolate this component from the total current. Linear sweep voltammetry (LSV) is the most commonly used potential sweep technique in measuring hydrogen crossover (Brooker et al, 2012;Giner-Sanz et al, 2014;Huang et al, 2013;Hwang et al, 2018;Kocha et al, 2006;Niroumand et al, 2015;Wasterlain et al, 2011), but different scan rates always give rise to inconsistent results. Another electroanalytical method as a derivative of LSV is staircase voltammetry (also called as potential step method [PSM]), in which the potential sweep is a series of stair steps, and it has been employed in electrochemical measurements of hydrogen crossover (Schoemaker et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous distributions of reactants within the FC stack can lead to uneven mass transport losses and the degradation of the membrane electrode assembly (MEA) through membrane thinning, while the localised build-up of water on the FC MEA results in droplet formation in the flow fields of the bipolar plates [22]. Water build-up can eventually lead to cell flooding and the formation of hotspots which can cause the formation of pin-holes, a major cause of FC failure [23].…”
Section: Introductionmentioning
confidence: 99%
“…Post-mortem open circuit voltage (OCV) monitoring has been used by several authors to identify failed cells within a stack, details of which have been used to characterise pinholes [22,23,32], whilst others have used segmented single cells to investigate differences in the current density in the presence of a pin-hole [13]. Commonly, small stacks of 5-18 cells are studied [33,34]; however, studies on automotive systems containing hundreds of cells are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of hydrogen that leaksthrough the membrane at a given dP to the cathode was measured as voltage, which was correlated to a specific leak rate. The relationship between the leak rate from anode to cathode and the flow rates and pressures is described below [113].where L is the leak rate (cm 3 -H 2 min -1 ), P c is the pressure at cathode, P a is the pressure at anode, Q N is the nitrogen flow rate at cathode, Q w is the water flow rate at the cathode, Q H is the hydrogen flow rate at cathode exit, P w is the saturation vapor pressure of water, Q H = L is the steady state mass balance on H 2 .The following linear relationship between leak rates and pressure is assumed: …”
mentioning
confidence: 99%
“…The amount of hydrogen that leaksthrough the membrane at a given dP to the cathode was measured as voltage, which was correlated to a specific leak rate. The relationship between the leak rate from anode to cathode and the flow rates and pressures is described below [113].…”
mentioning
confidence: 99%